Study Of Use Of Antituberculosis Drugs (OAT) In One Of The Hospitals In Jember District - Fitri Amirah Nahdah Salsabilah; Wima Anggitasari (Journal of Medical Laboratory in Infectious and Degenerative Diseases, 2025)
Abstract Background: Tuberculosis (TB) is a long-term infectious disease caused by the bacterium Mycobacterium tuberculosis. Successful management of pulmonary TB will reduce the rate of disease transmission and the risk of death. TB treatment is carried out routinely over a period of time under the supervision of a Drug Companion (PMO).] Purpose: This study aims to identify the type of TB treatment received by patients and the duration of treatment. Methods: This is a descriptive study. Data collection on study subjects was conducted retrospectively using medical records of TB patients undergoing anti-TB treatment (OAT) therapy from January to December 2023. Sampling used a purposive sampling technique, with a sample size of 73. Results: The study showed that the majority of patients were male (60.3%), and the majority were aged 17-25 years (32.9%). Most patients used FDC drugs with a treatment duration of 0-6 months. Conclusions: Most study subjects received anti-TB therapy with a treatment duration of 0-6 months.